(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Glycyrrhizic acid, water-soluble polysaccharides and pectin substances have been isolated from licorice root. Physical and chemical parameters, monosaccharide composition of water-soluble polysaccharides and pectin substances were studied. In the composition of carbohydrates, the predominant monosaccharides are uronic acids, galactose, glucose and arbinose, xylose and rhamnose are in trace amounts.